2020
DOI: 10.3389/fphar.2020.01090
|View full text |Cite
|
Sign up to set email alerts
|

A 7-Years Active Pharmacovigilance Study of Adverse Drug Reactions Causing Children Admission to a Pediatric Emergency Department in Sicily

Abstract: Children represent one of the most susceptible groups to adverse drug reactions (ADRs), as a consequence of physiological growth and maturation of different organ systems. The aim of this study was to characterize the frequency, preventability and seriousness of ADRs recorded in the Pediatric Emergency Department (ED) of the University hospital of Messina, in Sicily. All the suspected adverse reactions to drugs and vaccines collected from 2012 to 2018 were selected and then analyzed. Only adverse drug reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…In the current study, the Naranjo algorithm and WHO-UMC scales of causality assessment observed that most of the ADRs were probable/likely categories. Similar findings were also reported by Nasso et al, 2020 , Al-Damen and Basheti, 2019 , and Saqib et al, 2018 ). Because of their simplicity, the Naranjo algorithm and WHO-UMC scales are also used to evaluate the causality score in paediatric patients.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the current study, the Naranjo algorithm and WHO-UMC scales of causality assessment observed that most of the ADRs were probable/likely categories. Similar findings were also reported by Nasso et al, 2020 , Al-Damen and Basheti, 2019 , and Saqib et al, 2018 ). Because of their simplicity, the Naranjo algorithm and WHO-UMC scales are also used to evaluate the causality score in paediatric patients.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the observed rate of ADR related to paediatric patients was 1.7 ADRs per 1,000 admissions. Nasso et al also reported similar findings (1.6 ADRs/1,000 admissions) in paediatric patients (Nasso et al, 2020). However, another study conducted by Lombardi et al, observed 2.2 ADRs per 1,000 paediatric admissions, which was higher as compared to our study (Lombardi et al, 2018).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations